Death drive: A concept redefined - Castro, Elza Maria Neffa Vieira de; Castro, Pedro Aranha Neffa Vieira de (Seven Editora, 2024)
Based on individualism, determinism and the human-nature dualism, Freud affirmed the existence of an aggressive drive in psychic processes and theorized the integration of the subject in social life, from the perspective of opposition/domination, configuring the natural and insurmountable character of the death drive. In an attempt to overcome the dichotomy inherent in the concepts formulated in Freudian metapsychology, contemporary psychoanalytic theories, especially Winnicott’s, have revised the concept of the death drive and what gravitates around it. From this perspective, Winnicott interpreted the emergence of subjectivity from the interaction of the subject with the environment and aggressiveness as an expression of primary love, denying it as a manifestation of the instinctual movement that aims at destruction and death. For him, reliability and connection with the environment are fundamental conditions for the process of self-creation and transformation of the subject. From this perspective, Winnicott made the dynamics of the elements of the drive theory and the pleasure principle consonant with the complexity of current times. The bibliographic study, presented here, supports the construction of the theoretical-methodological framework of the analysis of the psychoanalytic theory and the unfolding of the Freudian inflection, based on the thought of the psychoanalyst Donald Winnicott, whose theory revised the idea of the death drive, formulated by Freud, in 1920, in Beyond the Pleasure Principle. As a result, the study points out elements to think about the conception of integrated nature, alien to the machinic metaphor, from the idea of a being capable of creation and self-transformation with its power to act. DOI:https://doi.org/10.56238/sevened2023.007-083